Chemical and functional properties of bovine and porcine skin gelatin - Raja Nhari, Raja Mohd Hafidz; Che Man, Yaakob; Ismail, Amin; Anuar, Noorfaizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The ability to compare bovine and porcine skin gelatin based on their amino acid composition, polypeptides pattern, bloom strength, turbidity and foaming properties were investigated. Amino acid composition of both gelatin showed that the content of glycine, proline and arginine in porcine gelatin were higher than bovine gelatin. However, the polypeptides pattern between both gelatin is closely similar. The bloom strength of porcine gelatin was higher than bovine gelatin from pH 3 to pH 10. Both gelatin possessed highest bloom strength at pH 9. The lowest bloom strength of bovine gelatin was at pH 3 while porcine gelatin at pH 5. The highest turbidity of bovine gelatin obtained at pH 7 while porcine gelatin at pH 9. Foam expansion and foam stability of bovine gelatin were higher than porcine gelatin at all concentrations.